Humor and the willingness to buy healthy food posted on Instagram - Reijnen, Ester; Laasner Vogt, Lea; Catarci, Daniele; Zengaffinen, Jean L.; Bremermann-Reiser, Sabine M.; Bläuer, Lars (Frontiers in Psychology, 2024)
Humorous messages (not derogatory jokes) related to obesity seem to be retweeted frequently. Potentially, such humor could be included in viral public health campaigns to combat obesity, but would jokes actually increase the likelihood of purchasing healthy foods advertised on social media? 411 participants were asked to test two soon-to-be-introduced features (e.g., repost button) in Instagram on their phones. Participants scrolled through a series of posts about various topics ranging from architecture to beauty products. A healthy food post, preceded by one of four joke types (two containing the word “fat”), was embedded at the top, middle or bottom position of the Instagram page. After participants scrolled through the page, perhaps reposting some posts, they were presented with the healthy food product featured in the post and were asked to indicate a purchase probability (0–100), as well as whether they recognized the food product from the post (yes/no). At the end of the study, the individual jokes were rated as “funny/not funny” and “positive/negative”. If the food product was recognized, the joke type played a role. In particular, jokes containing the word “fat” had a negative effect on the purchase probability. However, if the food product was not recognized, only its position on the page mattered. The purchase probability was highest if the product was placed at the top. Social media, criticized for promoting unhealthy food consumption, especially among children, can therefore also be used to address issues such as the global obesity epidemic.